Effect of dietary polyphenols along with exercise on hepatic transcriptional regulators of lipid metabolism - Han, YiXiao; Chen, ZhiHao (Frontiers in Nutrition, 2025)
The increasing dangers of aging dyslipidemia, such as cardiovascular disease, which is one of the major causes of mortality globally, must be prevented and managed due to the detrimental consequences of age-associated dyslipidemia, particularly its dangerous effects on the cardiovascular system. Numerous studies have shown that various forms of physical activity, including strength training and moderate aerobic workouts, have a good impact on middle-aged, adult, and elderly people’s lipid profiles, inflammatory responses, and cardiovascular risk. Besides exercise, natural substances found in fruits and plants, including polyphenols which have anti-inflammatory and antioxidant qualities, can also enhance health and slow down the effects of aging on changes in lipid profiles and cardiovascular irregularities. The impact of aging-related liver disease and dyslipidemia on cardiovascular abnormalities in the older population have been the subject of several research over the past 40 years. The precise mechanism of aging on the particular molecular mediators implicated in dyslipidemia in older adults has seldom been studied, despite the fact that several elements of the detrimental effects of aging on liver structure and function have been previously documented. Thus, in this study, we looked at how natural products and exercise affect hepatic transcriptional variables related to lipid metabolism.